1000 Action words - Zain, Shama (Karachi : Paramount books Ltd, 2021)
Paramount 1000 words series is a collection of three delightful books designed for young and curious minds. The basic purpose of developing this series is to help kids discover the world. Children will learn by exploring their own self and the environment around them. These books consist of objects and scenarios related to a child's day to day life, surroundings, neighborhood and outer world. All the books are accompanied with eye-catching pictures and illustrations, arranged in visually appealing way to grab the attention of readers. Children will be able to analyze the pictures to understand the meaning and concept of each word. These books will also help the kids to expand their vocabulary by learning new words. Interesting themes and characters are designed to make learning fun. Different activities are included to make the children think more deeply. This series is ideal for primary grades and prepared according to the latest learning guidelines. It will be an enjoyable experience for kids and can be used at school or home.
"Paramount 1000 Action Words" by Shama Zain appears to be an educational resource focused on building vocabulary related to actions or verbs. The book likely uses illustrations to depict various actions, making it easier for young learners to understand their meaning. By visually associating words with corresponding activities, it aims to enhance comprehension and language development in children. This approach can be particularly helpful for early literacy
Keywords: Action word book